AUTOMATION AND GAMIFICATION OF COMPUTER SCIENCE STUDY - ZSIGMOND, Imre (Studia Universitatis Babeș-Bolyai Informatica, 2019)
A large part of the job of a university teacher in computer science is to verify student exercises. The task of verifying correctness, coding style, conventions, and grading is laborious and if done correctly leaves little time for questions. Automating aspects of this work helps all parties involved by freeing time up for questions. The solution detailed in the paper automates a number of these tasks and provides near instant feedback for the students, together with a platform to gamify student learning.